STUDI KELAYAKAN PENYERTAAN MODAL KABUPATEN PEKALONGAN KEPADA PIHAK KETIGA - Mahirun Mahirun; Akhmad Sakhowi (LPPM Universitas Pekalongan, 2018)
This study aims to examine the investment feasibility of Pekalongan Regency Government to third parties. Objects of this study are Bank Central Java, BPR BKK Bank Pekalongan Regency, BKK Kajen, and PDAM Tirta Pekalongan Regency. Data analysis tool uses Average Rate of Return, Net Present Value and Internal Rate of Return. The results showed that Bank Jateng, the feasibility study of the capital participation of the Regency of Nomenclature to PT Bank Jateng was feasible with ARR reaching an average of 129.33%, the IRR reaching 62.50%, and a positive NPV of Rp. 56,626,000,000. BPR BKK Pekalongan Regency, the feasibility study of equity participation in Peklaongan Regency to BPR BKK in Pekalongan Regency is feasible to be carried out with ARR reaching an average of 50.18%, IRR reaching 14.10%, and positive NPV of Rp. 2,851,417,641. BKK Kajen, the feasibility study of the equity participation of Peklaongan Regency to the BKK Kajen is feasible to carry out with ARR reaching an average of 10.04%, the IRR reaching 5.16%, and a positive NPV of Rp 20,474,809. PDAM Tirta Pekalongan Regency, the feasibility study of the equity participation of Peklaongan Regency to PDAM Tirta in Pekalongan Regency is feasible to be carried out with ARR reaching an average of 24.43%, an IRR of 19.48%, and a positive NPV of Rp. 2.711,894,398.